Implementación de una aplicación web para la gestión de venta de productos en el Depósito de Cerveza “Palmito”, cantón Montalvo, provincia Los Ríos, año 2023. - Nuñez Aguila, Ariel Sebastian (2023)
The development of software for different areas and specifically in commerce has allowed small, medium and large companies to grow and access other markets, something that is very difficult to achieve in the traditional way and that currently with the implementation of the e-commerce system is more simple. The primary objective of this titling project was to implement a web application for the commercialization of products from the Palmito beer warehouse, in the Montalvo canton, Los Ríos province, in order to promote the growth and advertising of the beer warehouse that it offers. liquor store products, in addition to providing solutions to electronic payment problems and business sales reports. For the development of the application, we worked under the Extreme Programming development methodology, using a capable architecture, PHP programming language, MariaDB database and an Apache web server. The Palmito web application has modules for managing products, users and electronic payments through deposits and transfers. Also, the document includes the techniques and instruments for data collection, specification of feasibility requirements, tests performed, user manual for the client and administrator. Thus, the final result of the Palmito beer warehouse streamlines the trade of its products within its city with the use of the system. Keywords: Electronic Commerce, Electronic Payments, Computer Systems, Extreme Programming.